Chlorurus rhakoura Randall & Anderson, 1997 (Perciformes, Scaridae), an Indo-Pacific fish new for the Mediterranean Sea - INSACCO, G.; ZAVA, B. M. (Mediterranean Marine Science, 2017)
The scarid fish Chlorurus rhakoura Randall & Anderson, 1997, of eastern Indo-Pacific origin, is recorded for the first time from the Mediterranean Sea. A small school of six individuals of this species were caught off Portopalo, Sicily, Italy in February 2017. Morphometric measurements and meristic traits are provided based on four specimens, and the possible vector of introduction of the species into the Mediterranean is briefly discussed.